Complete Pathological Response to Neoadjuvant Pembrolizumab in a Patient With Chemoresistant Upper Urinary Tract Urothelial Carcinoma: A Case Report - Ikarashi, Daiki; Kitano, Shigehisa; Ishida, Kazuyuki; Nakatsura, Tetsuya; Shimodate, Hitoshi; Tsuyukubo, Takashi; Tamura, Daichi; Kato, Renpei; Sugai, Tamotsu; Obara, Wataru (Frontiers in Oncology, 2020)
Treatment options as second-line therapy for advanced ureteral carcinoma are limited and patients experiencing recurrence after first-line cisplatin-based chemotherapy and have a poor prognosis. Recently, the PD-1 inhibitor pembrolizumab provided better survival benefit with complete response rate (9.2%) for chemoresistatant urothelial carcinoma. However, the dynamic change of cancer microenvironment about the cases of complete response are still unknown. We herein report a case of 57-year-old man who had been diagnosed with localized, non-muscle invasive bladder cancer (pT1N0M0, high grade), for which he underwent transurethral resection of the bladder cancer twice. Given that gemcitabine plus carboplatin as first-line neoadjuvant chemotherapy was unable to control left vesico-ureteral junction recurrence with muscle invasion (T3N0M0, high grade), the patient received the PD-1 inhibitor pembrolizumab as second-line neoadjuvant therapy in an attempt to stop tumor growth, which promoted dramatic tumor shrinkage without serious adverse effects and allowed subsequent nephroureterectomy and lymphadenectomy. To the best of our knowledge, this has been the first study to report that pembrolizumab administration before surgery for chemotherapy-resistant ureteral carcinoma promoted pathological complete response, and to better understand the cancer microenvironment after immunotherapy.